A unique flipped classroom approach shows promising results in physician assistant education. (3rd March 2020) - Deshpande, Saarang; Ritzenthaler, David; Sun, Alec; Rudert, Nicole; Lewis, Jensen
Abstract: Aims: The flipped classroom (FC) model utilizes pre-class foundational learning with in-class higher-order application exercises. FC approaches have reported positive perceptions and mixed academic performance outcomes in medical education; however, little evidence exists on their impact in the 56-week didactic curriculum of Physician Assistant (PA) education. Methods: A 4-week FC curriculum was piloted in a PA behavioral medicine course ( n  = 34). Before class, students completed online video modules. During class, students completed a pre-class quiz and answered clinical case-based questions in a think-pair-share format. Results: Students rated in-class time higher than a lecture-based segment of the same course ( p  = 0.028). Assessment of achievement emotions demonstrated increased enjoyment ( p  = 0.028) and decreased boredom ( p  < 0.001) in the FC curriculum with no difference in anxiety. The FC curriculum produced a 57.2 min increase in pre-class preparation time with no change in post-class studying time. Compared to historical lecture-based controls ( n  = 35), students in the FC curriculum scored significantly higher on clinical vignette questions ( p  = 0.019) with equivalent performance on other question formats. Conclusions: This study offers the first positive outcomes of an FC approach in PA education and provides a framework for improving academic performance while scaling back in-class time.